2005
DOI: 10.1261/rna.7251305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of a synthetic tetracycline-binding riboswitch

Abstract: Riboswitches are newly discovered regulatory elements that consist solely of RNA, sense their ligand in a preformed binding pocket, and perform a conformational switch in response to ligand binding, resulting in altered gene expression. Regulation by a tetracycline (tc)-binding aptamer when inserted into the 5 untranslated region (UTR) of a reporter gene exhibits all characteristics of a riboswitch. Chemical and enzymatic probing reveals that the aptamer consists of two stems, P1 and P2, which are already pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 32 publications
(31 reference statements)
4
88
1
Order By: Relevance
“…This contact might be disturbed in the spin labeled aptamer conformation. However, it has been shown that nucleotide exchanges on position 12 retain the regulatory activity of the aptamer (Hanson et al 2005), and the Tc-binding constants for FIGURE 1. Secondary structure predicted for the Tc aptamer according to Hanson et al (2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contact might be disturbed in the spin labeled aptamer conformation. However, it has been shown that nucleotide exchanges on position 12 retain the regulatory activity of the aptamer (Hanson et al 2005), and the Tc-binding constants for FIGURE 1. Secondary structure predicted for the Tc aptamer according to Hanson et al (2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that nucleotide exchanges on position 12 retain the regulatory activity of the aptamer (Hanson et al 2005), and the Tc-binding constants for FIGURE 1. Secondary structure predicted for the Tc aptamer according to Hanson et al (2005). Thiouridines (U) spin labeled with MTS are marked by full gray circles, 29-aminouridine labeled with 4-isocyanato-TEMPO are depicted by open gray circles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting PCR product covers the entire 59 UTR with the aptamer and the first 48 nt of the gfp coding region. RNA transcripts were dephosphorylated and subsequently 59-32 P-end labeled as previously described (Hanson et al 2005). RNA (100,000 cpm) was incubated in 50 mM sodium acetate (pH 4.5), 280 mM NaCl, 4.5 mM ZnSO 4 (S1), or 50 mM Tris-HCl (pH 7.5) (T1) for 2 min at 56°C and for 10 min at 37°C.…”
Section: Enzymatic Probing Of Aptamer Rnamentioning
confidence: 99%
“…These findings suggest a strong interaction with TC and thus a dramatic, positive change in H. Nucleotides A52 and U54 show a positive entropy difference inside L3. Interestingly, molecular probing experiments show that G51, A52, and U54 of L3 are-in the absence of the antibiotic-the most modified nucleotides [23,34]. Clearly, they change their conformational flexibility upon ligand binding due they direct interaction with the solvent.…”
Section: Application To Molecular Synthetic Biologymentioning
confidence: 99%